The Archaeology of Motzki’s Studies on Hadith: Study of The Origin of Isnad Cum Matn Method - Imam Sahal Ramdhani (Millati: Journal of Islamic Studies and Humanities, 2021)
Hadith studies, especially the discourse of the dating of hadith, become Western Scholarship's concern. Some of them include the Revisionist or the Skeptic group such as Ignaz Goldziher, Joseph Schacht, Juynboll, Michael Cook, Patricia Crone, Norman Calder, and others. Their paradigm, idea, and theory dominate around the hadith studies. This domination spread not only in Europe but also in other areas. Then Harald Motzki, as one of the Sanguine group members, challenges their idea and paradigm with his theory, the Isnad Cum Matn method. This method is combined both The Revisionist method and The Sanguine method. It is essential to investigate the nature of the Isnad Cum Matn method and the genesis of this discourse. The questions now present itself; what is the epistemological structure of Motzki's study on hadith? What is the archaeological dimension of the Isnad Cum Matn method? This research uses epistemology, genealogy, and the archaeology of knowledge as the analytical theory. The type of this research is library research. The source of the primary data of this research is from two of Motzki's main book. There are The Origins of Islamic Jurisprudence Meccan Fiqh before The Classical School and Analyzing Muslim Tradition. The data analysis is described by descriptive method, taxonomy method, interpretative method, and the comparative method. Based on this research, we can conclude several points.The first is that the Isnad Cum Matn's epistemological structure relies on the source, the methodology, and validity. The Isnad Cum Matn method's source comes from the classical hadith collection, the transmitter's biography, and the Western scholars' theories. The methodology of the isnad cum matn shows the combination between the Revisionist and the Sanguine theories. The Isnad Cum Matn method's validity depends on the historical data of the transmitter, the structural correspondences of the bundle of isnad, and the connections of Mutun. The second is that the Isnad Cum Matn method is not built from a "space," but this method's nature came from many aspects offered by many scholars. The discourse formation of the dating hadith issue shows that his theory connected to many scholars' theories before him. The discourse appears by the relation among scholars (geo-academical scholars) and the political factor. The discourse of the Isnad Cum Matn is constructed by the hegemony of the Sanguine paradigm. The characteristic of this paradigm is anti-Eurocentrism, self-reflective, and self-critics. The Sanguine paradigm is controlled by the Sanguine scholars who relate with Deutsche Morgenlandischen Gessellschacft and the Albert Hourani Award.